Pengaruh Perilaku Inovatif, Iklim Organisasi Sekolah Serta Teacher Engagement Terhadap Task Performanced di Sekolah XYZ Jakarta - Merry Christiana (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2022)
The success of a school is highly influenced by the task performance of its teachers. Teachers' task performance is associated with various factors, including teachers’ innovative behavior, the organizational climate of the school, and teacher engagement. This study aims to examine the influence of teachers' innovative behavior, school organizational climate, and teacher engagement on teachers' task performance. The research subjects consist of one hundred and fifteen teachers teaching from early childhood education to senior high school levels at an XYZ Cooperation Education Unit (SPK) school in Jakarta. The research design used is path analysis with a quantitative approach. The findings indicate that innovative behavior has a positive influence on teachers' task performance, organizational climate has a positive influence on teachers' task performance, and teacher engagement also has a positive influence on teachers' task performance. These results emphasize that schools need to create a supportive organizational climate, encourage teachers to be innovative in their teaching practices, and strengthen teacher engagement in order to maximize overall performance. In addition, the study highlights the interconnected role of innovation, climate, and engagement as key determinants of effective task performance. Strengthening these factors will ultimately contribute to improving the quality of education and the overall success of schools.